Osmotic Shock Inhibits Insulin Signaling by Maintaining Akt/Protein Kinase B in an Inactive Dephosphorylated State - Chen, Dong (American Society for Microbiology, 1999)
We have previously reported that insulin and osmotic shock stimulate an increase in glucose transport activity and translocation of the insulin-responsive glucose transporter isoform GLUT4 to the plasma membrane through distinct pathways in 3T3L1 adipocytes (D. Chen, J. S. Elmendorf, A. L. Olson, X. Li, H. S. Earp, and J. E. Pessin, J. Biol. Chem. 272:27401–27410, 1997). In investigations of the relationships between these two signaling pathways, we have now observed that these two stimuli are not additive, and, in fact, osmotic shock pretreatment was found to completely prevent any further insulin stimulation of glucose transport activity and GLUT4 protein translocation. In addition, osmotic shock inhibited the insulin stimulation of lipogenesis and glycogen synthesis. This inhibition of insulin-stimulated downstream signaling occurred without any significant effect on insulin receptor autophosphorylation or tyrosine phosphorylation of insulin receptor substrate 1 (IRS1). Furthermore, there was no effect on either the insulin-stimulated association of the p85 type I phosphatidylinositol (PI) 3-kinase regulatory subunit with IRS1 or phosphotyrosine antibody-immunoprecipitated PI 3-kinase activity. In contrast, osmotic shock pretreatment markedly inhibited the insulin stimulation of protein kinase B (PKB) and p70S6 kinase activities. In addition, the dephosphorylation of PKB was prevented by pretreatment with the phosphatase inhibitors okadaic acid and calyculin A. These data support a model in which osmotic shock-induced insulin resistance of downstream biological responses results from an inhibition of insulin-stimulated PKB activation.